Visualisasi Konsep Barisan Bilangan Real - Hadi, Syaiful (Ta'allum: Jurnal Pendidikan Islam, 2014)
A sequence of real numbers ( a sequence in R) is a function defined on the set N of natural numbers whose range is contained in the set R of real numbers. The concept of sequence can be visualized as a graph of special functions with domain on the set N and range is contained in the set R. Visualization is a bridge for students who are in transition to formal thinking.